Comparative image analysis approaches to assess ecological effects of macroalgal removal on inshore reefs of Magnetic Island, Australia. Issue 1 (1st January 2023) - Hermanto, B; Bourne, D G; Smith, H
Abstract: Macroalgae removal is a proposed management option in the GBR to reverse declines in inshore coral reef health. Automated image analysis (AIA) is a valuable tool to assess benthic community assemblages. This study compared the accuracy of benthic community assemblages assessed through the AIA program CoralNet to manual image analysis. The ecological effect of macroalgae removal on benthic community composition was also investigated on established permanent quadrats (5x5 m) for reefs at Florence and Arthur Bay, Magnetic Island. Control and treatment quadrats (n=3 respectively) were photographed before and after macroalgae removal over 6 months. The results obtained by AIA and manual approaches were consistent, with macroalgae cover is approximately 77%-87% in all quadrats before macroalgal removal. Through the monitoring period, a small increase in coral cover in the macroalgal removal quadrats was observed in Florence and Arthur Bay (an increase of 1.8% and 0.1%, respectively). CoralNet was demonstrated to be robust for assessing reef benthic cover with no significant difference in recorded benthic categories when compared to the manual approach. CoralNet was accurate for identifying broad benthic categories, but less effective than manual image analyses for lower taxonomic categories (i.e., genus or species level).